Impact of psychological wellbeing and academic readiness on early medical student attrition: educators’ perspective - Ashraf F. Hefny; Mohi Eldin Magzoub; Nirmin A. Mansour; Sherif A. Fathi; Omran Bakoush (BMC Research Notes)
Abstract Objectives Medical school attrition is a complex problem, and improvement can only be achieved through the integrated involvement of all stakeholders. Mental health disorders are perceived to be prevalent among medical students in UAE. This study aimed to explore educators’ perspectives on the high rate of early medical school attrition in UAE. Results The findings suggest that the early medical school attrition rate is correlated with students’ inadequate academic readiness and their inability to cope with the psychological demands of studying medicine in English. To reduce the attrition rate, the educators proposed preparatory courses to enhance students’ self-learning skills and academic readiness for university studies, along with provision of targeted academic support throughout their medical studies. Psychological well-being and academic preparedness for studying medicine in English is a prime target for a program to reduce dropout from medical schools.